Filsafat Pendidikan Politik Plato Sebagai Cara Untuk Menyiapkan Calon Pemimpin Indonesia - Andika Setiawan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This study seeks to review how to formulate educational programs to prepare potential ideal leaders amid Indonesia's learning problems which are only limited to rote practice. This phenomenon results in students having little or no reasoning power. Moreover, many state officials have committed criminal acts of corruption so that students seem not to have moral role models. This teaching problem, in essence, can be prevented by Plato's philosophy of political education. This study is descriptive qualitative research. Data collection was obtained from the literature. Primary data is taken from The Republic Plato, and secondary data includes books, journals, magazines, mass media, and writings relevant to the subject matter of the discussion. From the sources that have been collected, it is then presented and then analyzed/dialogued in such a way and a conclusion is drawn. Based on the results of observations on Plato's political education philosophy, the results obtained include; the domain of discussion refers to the human soul, so in terms of education, it presupposes mousike, gymnastike, and dialectic programs. Also the allegory of the cave that Plato used to criticize the Sophists and describe the struggles of gaining knowledge. Then analyzed, and then integrated with the 2013 curriculum, resulting in educational programs: reading of Al-Barzanji text - for Muslims - or spiritual songs - for non-Muslims; martial arts; Discussion in each learning session. From there it is hoped that the ideal leader for Indonesia will emerge. Keywords: Leader, Philosophy of Political Education Plato, Education Program. Kajian ini berusaha mengulas bagaimana cara merumuskan program pendidikan untuk menyiapkan calon pemimpin ideal di tengah problematika pembelajaran Indonesia yang hanya terbatas pada praktik hafalan. Fenomena ini mengakibatkan anak didik memiliki sedikit daya nalar bahkan tidak memiliki sama sekali. Terlebih, banyak pejabat negara yang melakukan tindak pidana korupsi sehingga anak didik seperti tidak memiliki figur teladan moral. Permasalahan pengajaran tersebut, pada hakikatnya dapat dicegah dengan filsafat pendidikan politik Plato. Kajian ini merupakan penelitian kualitatif deskriptif. Pengumpulan data diperoleh dari kepustakaan. Data primer diambil dari The Republic Plato, dan data sekunder meliputi buku, jurnal, majalah, media massa, serta tulisan yang relevan dengan tajuk pembahasan. Dari sumber-sumber yang telah terkumpul, kemudian disajikan lalu dianalisis/didialogkan sedemikian rupa dan ditarik pada suatu kesimpulan. Berdasarkan hasil pengamatan terhadap filsafat pendidikan politik Plato, yang diperoleh meliputi; domain pembahasan merujuk pada jiwa manusia, sehingga dalam hal pendidikan, mengandaikan program mousike, gymnastike, dan dialektika. Juga alegori gua yang digunakan Plato untuk mengkritik kaum Sofis dan menggambarkan perjuangan saat menimba ilmu pengetahuan. Selanjutnya dianalisis, dan kemudian diintegrasikan dengan kurikulum 2013, sehingga menghasilkan program pendidikan: pembacaan teks Al-Barzanji–untuk muslim–atau lagu-lagu rohani–untuk non-muslim; pencak silat; Diskusi di setiap sesi pembelajaran. Dari sana diharapkan muncul pemimpin ideal bagi Indonesia. Kata Kunci: Pemimpin, Filsafat Pendidikan Politik Plato, Program Pendidikan.